The Basketball-20: Developement of a basketball-specific field-based work protocol - Nigg, S.; Whitting, J.; Tomaras, E.; Davis, E.; Nigg, B. (Journal of Fitness Research, 2015)
Introduction: Basketball is a popular sport that has been studied extensively to determine player position and game profiles and factors related to injury risk and performance. However, no research has developed or used a comprehensive field-based protocol, designed to simulate game-like effort using basketball specific drills, for the assessment of relevant physiological outputs. The objective of this project, therefore, was to develop a repeatable basketball-specific field-based work protocol (Basketball-20) designed to simulate game-like effort and conditions for the assessment of physiological outputs in basketball athletes.